Implementation of the Classical Learning Model in Kindergarten - Lina (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The aim of this research is to describe the implementation of the classical learning model in kindergarten. Methodology: The method used in this research is descriptive quantitative and qualitative using questionnaires, observations and interviews as data collection techniques. Analysis of questionnaire and observation data uses statistical techniques, while interviews use interactive analysis. Main Findings: The implementation of the classical learning model in kindergarten is of